The effect of oxidation on the stability of G-quadruplex DNA : implications for oncogene expression - Stebbeds, William Joshua David (Cranfield University, 2011)
G-quadruplexes (G4-DNA) are a class of secondary structures formed from Guanine rich sequences. In recent years these structures have been implicated in both telomere maintenance and oncogene expression, and have been shown to be abundant in upstream promoter regions and at telomeric ends. The mutagenic properties of oxidative stress on DNA have been widely studied, as has the association with carcinogenesis. The oxidation of deoxyguanosine to 8-oxo-2’deoxyguanosine (8-oxo-dG) is the most common result when DNA is under oxidative stress and as such, the G-rich sequences that form G-quadruplexes can be viewed as potential “hot-spots” for DNA oxidation. We propose that oxidation may destabilise the G-quadruplex structure, leading to its unfolding into the duplex structure, affecting gene expression. This would imply a possible mechanism by which oxidation may impact on oncogene expression. This project used both in silico and in vitro methods to observe the effect of oxidation on the G-quadruplex structure and the consequences in oncogene expression, using two biologically relevant G-quadruplex structures, those found in the promoter regions of the proto-oncogenes c-Myc and c-Kit as proof of concept. Molecular dynamics (MD) simulations were performed (isothermic, isobaric 500ns unrestrained simulation in explicit solvent and counterions) on the c-Kit and c-Myc G-quadruplex structures with and without 8-oxo-dG incorporated into the central tetrad. FRET experiments were performed on these same structures, observing the conformation of sequences known to form G-quadruplexes under near physiological conditions and subjected to oxidative stress, through Fenton chemistry. Gene expression data analyses were also performed to evaluate the prevalence of different G-quadruplex forming motifs (GQMs) in genes affected by oxidation.Although no relevant information was gained from the FRET experiments, the MD results constitute the longest simulations of this type performed on the c-Myc and c-Kit G-quadruplex structures published to date and predict the high stability of these structures under normal physiological conditions. They also clearly demonstrate a destabilising effect of oxidation on G-quadruplex structures, with the extent of the effect dependent on the structure oxidised. Furthermore, gene expression data analysis showed that genes whose expression is significantly altered when subjected to oxidative stress are statisticallymore likely to contain a GQM than the remainder of the genome, through the use of significance testing. These findings demonstrate a differential effect of oxidation on G-quadruplexes, likely dependent on other known characteristics affecting G4 stability such as loop length and sequence. Results also point towards this mechanism affecting gene expression. This is suggestive of a novel route for oxidation mediated carcinogenesis, through upregulation of oncogene expression or possibly downregulation of tumour suppression genes.
Keywords: G-quadruplexes; G-quadruplexes; oncogene expression; Carcinogenesis; C-Myc; c-Kit